Novel cancer gene discovery using a forward genetic screen in RCAS-PDGFB-driven gliomas. Issue 1 (23rd June 2022) - Weishaupt, Holger; Čančer, Matko; Rosén, Gabriela; Holmberg, Karl O; Häggqvist, Susana; Bunikis, Ignas; Jiang, Yiwen; Sreedharan, Smitha; Gyllensten, Ulf; Becher, Oren J; Uhrbom, Lene; Ameur, Adam; et al.
Abstract: Background: Malignant gliomas, the most common malignant brain tumors in adults, represent a heterogeneous group of diseases with poor prognosis. Retroviruses can cause permanent genetic alterations that modify genes close to the viral integration site. Methods: Here we describe the use of a high-throughput pipeline coupled to the commonly used tissue-specific retroviral RCAS-TVA mouse tumor model system. Utilizing next-generation sequencing, we show that retroviral integration sites can be reproducibly detected in malignant stem cell lines generated from RCAS-PDGFB-driven glioma biopsies. Results: A large fraction of common integration sites contained genes that have been dysregulated or misexpressed in glioma. Others overlapped with loci identified in previous glioma-related forward genetic screens, but several novel putative cancer-causing genes were also found. Integrating retroviral tagging and clinical data, Ppfibp1 was highlighted as a frequently tagged novel glioma-causing gene. Retroviral integrations into the locus resulted in Ppfibp1 upregulation, and Ppfibp1 -tagged cells generated tumors with shorter latency on orthotopic transplantation. In human gliomas, increased PPFIBP1 expression was significantly linked to poor prognosis and PDGF treatment resistance. Conclusions: Altogether, the current study has demonstrated a novel approach to tagging glioma genes via forward genetics, validating previous results, and identifying PPFIBP1 as a putative oncogene in gliomagenesis.